Pt(II)-Thiocarbohydrazone Complex as Cytotoxic Agent and Apoptosis Inducer in Caov-3 and HT-29 Cells through the P53 and Caspase-8 Pathways - Abeer A. Ibrahim; Mohanad M. Kareem; Taghreed H. Al-Noor; Tahani Al-Muhimeed; Abeer A. AlObaid; Salim Albukhaty; Ghassan M. Sulaiman; Majid Jabir; Zainab J. Taqi; Usama I. Sahib (MDPI AG, 2021)
In this study, a platinum(II) complex ([Pt(H2L)(PPh3)] complex) containing a thiocarbohydrazone as the ligand was tested as an anti-proliferative agent against ovarian adenocarcinoma (Caov-3) and human colorectal adenocarcinoma (HT-29) through MTT assays. Apoptotic markers were tested by the AO/PI double staining assay and DNA fragmentation test. Flow cytometry was conducted to measure cell cycle distribution, while the p53 and caspase-8 pathways were tested via immunofluorescence assay. Results demonstrated that the cytotoxic effect of the Pt(II)-thiocarbohydrazone complexes against Caov-3 and HT-29 cells was highly significant, and this effect triggered the activation of the p53 and caspase-8 pathways. Besides, apoptosis stimulated by the Pt(II)-thiocarbohydrazone complex was associated with cell cycle arrest at the G0/G1 phase. These findings suggest that the target complex inhibited the proliferation of Caov-3 and HT-29 cells, resulting in the arrest of the cell cycle and induction of apoptosis via the stimulation of the p53 and caspase-8 pathways. The present data suggests that the Pt(II)-thiocarbohydrazone complex could also be a promising chemotherapeutic agent for other types of cancer cells.